Kegiatan Nelayan Sebagai Ide Penciptaan Kriya Kayu Dengan Teknik 3D Wood Shadow Box Untuk Hiasan Dinding - Ilham Pratama (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The aim of making this final work is to convey life lessons, as well as introduce new techniques in the world of crafts, which are then expressed through the work in the form of visuals of fishermen's activities. The method of creation in this final work is carried out in stages, namely: the preparation stage is observations related to ideas and concepts of the author's interest, elaboration is the stage of exploring and displaying the diversity of fishing activities in terms of field surveys and electronic media, synthesis is the creation of an idea for a work , the realization of the concept is a stage of the work process and the completion or finishing of the work. Based on the method used, a work was created in the form of a wall decoration with fishermen's activities as the main object, which was made using the 3D Wood Shadow Box technique. The author created seven works with the titles: "Hope", "Reap", "Adrift", "Congratulations", "Shoulder to shoulder", "Rich", and "Alhamdulillah".